MEASURING THE EFFECTIVENESS OF PEDAGOGICAL DIAGNOSTICS THROUGH ARTIFICIAL INTELLIGENCE: RESEARCH AND PRACTICAL ANALYSIS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This scientific article explores methods for evaluating the effectiveness of artificial intelligence (AI)-based diagnostic systems in education. Through statistical data and comparative analysis, it highlights the advantages and disadvantages of AI-based diagnostic systems compared to traditional methods. The results aim to contribute to the improvement of educational assessment tools using AI technologies.